Semantic web reasoning tutoring agent - Panayiotou, Christiana; Bennett, Brandon (My University, 2008)
This paper proposes a proof theoretic approach to check conflicts between the arguments derived from the ontologies of learning resources. Two types of arguments that can arise in a situation where a learner encounters conflicting viewpoints about a topic are identified, namely syllogistic arguments and arguments about the set of necessary and sufficient conditions that represent a concept. A method based on set equations is applied to create Syllogistic arguments from ontologies. The taxonomic associations of concepts in Ontologies, can be converted to categorical statements giving rise to syllogisms. We also consider arguments about the necessary and sufficient features for the representation of concepts and show that they can be handled in a very similar way as syllogistic arguments. The approach can be applied by a pedagogical agent in an interactive learning environment in order to identify, discuss differences in conceptualizations and check the validity of claims of different resources. © 2008 Springer-Verlag Berlin Heidelberg.
Keywords: Combines; Computers; Glass